2016
DOI: 10.1086/689590
|View full text |Cite
|
Sign up to set email alerts
|

Protein Corona Modulates Uptake and Toxicity of Nanoceria via Clathrin-Mediated Endocytosis

Abstract: Particles present in diesel exhaust have been proposed as a significant contributor to the development of acute and chronic lung diseases, including respiratory infection and allergic asthma. Nanoceria (CeO2 nanoparticles) are used to increase fuel efficiency in internal combustion engines, are present in exhaust fumes, and could affect cells of the airway. Components from the environment such as biologically derived proteins, carbohydrates, and lipids can form a dynamic layer, commonly referred to as the "pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 58 publications
5
47
0
Order By: Relevance
“…This is in accordance with other results investigating the time and concentration dependence of uptake for a variety of NPs (e.g. polystyrene and gold) and cell lines (Johnston et al 2010;Trono et al 2011;Smith et al 2012;Mazzolini et al 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with other results investigating the time and concentration dependence of uptake for a variety of NPs (e.g. polystyrene and gold) and cell lines (Johnston et al 2010;Trono et al 2011;Smith et al 2012;Mazzolini et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Tf is known to bind to many different NPs and thus may offer a mechanism of entry for corona coated SPIONs in these cell types (Raynal et al 2004;Arbab et al 2005). Corona studies performed on the SPIONs used here identified the presence of Tf, indicating this as a potential mechanism of entry into the THP-1 cells through the CME pathway (Supplementary Figure S8); likewise the presence of Tf bound to CeO 2 NPs has been shown to be involved in receptor mediated endocytosis via CME (Mazzolini et al 2015).…”
Section: Mechanism Of Spion Uptake Into Different Cancer Cell Lines: mentioning
confidence: 66%
See 1 more Smart Citation
“…Jiang et al proved that zwitterionic quantum dot nanoparticles enter mainly via the clathrin‐mediated endocytosis. Mazzolini et al results identify a specific receptor‐mediated mechanism of CeO 2 nanoparticles. After the NPs enter the cells, they go through early endosome and late endosomes, locate in the lysosomes, and finally excrete from cells by lysosomes.…”
Section: Resultsmentioning
confidence: 98%
“…Endocytic trafficking involves a series of steps including endocytosis, cargo sorting and processing, intracellular membrane fusion and fission, vesicle mobility, and exocytosis [35]; the endocytic pathways include clathrin-dependent endocytosis, caveolae-dependent endocytosis, macropinocytosis, and phagocytosis. Recently, the pathways of clathrin and caveolae receptor-mediated endocytosis were well studied in cellular membrane trafficking for cancer therapy [36,37,38,39]. …”
Section: Introductionmentioning
confidence: 99%